Dokąd może zaprowadzić jeden wiersz barokowego poety? - Jarczykowa, Mariola (Śląskie Studia Polonistyczne, 2013)
The review underlines the cognitive and aesthetic values of Małe folio (historia jednego wiersza), a book by Mrowcewicz who interprets the poem Na oczy królewny angielskiej, która była za Fryderykiem, falcgrafem reńskim, obranym królem czeskim by Daniel Naborowski in many ways. The researcher contrasted the poem by a Polish poet with the French original by Honorat de Porcheres Laugier, pointed to significant differences between the texts, and derived European contexts from both works. Bringing the characters of the poem closer, Mrowcewicz used unpublished sources, and successfully chose illustrations presenting the people and events in question. The review paid attention to archive records concerning the English princess to be found in Radziwiłł’s property that Mrowcewicz did not use. The author of Małe folio, in his essayistic form, offers readers interesting research hypotheses concerning Naborowski’s contacts with Shakespeare, a magic garden of the Brotherhood of Rose’s Knight in Heidelberg, as well as Radziwiłł’s connections with European courts, which has not been the subject of academic reflections so far, and constitutes a great value of the publication.